PENGARUH TAX AVOIDANCE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN LEVERAGE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2018) - Muhammad Rizal Saragih; Rusdi Rusdi (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to analyze the effect of tax avoidance and dividend policy on firm value with leverage as a moderating variable. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 consisting of 166 companies, while the sample of this study is 18 companies with sampling using purposive sampling method. The research method used is descriptive statistics, testing classic assumptions and hypothesis testing multiple linear regression analysis The results showed that tax avoidance has no effect on firm value, dividend policy has an effect on firm value, leverage does not moderate tax avoidance on firm value, leverage does not moderate dividend policy on firm value, and tax avoidance and dividend policy have an influence on firm value.